Efektivitas Sistem Pengendalian Mutu dalam Menjaga keberlanjutan Pendidikan Nonformal - Fudla Afiyati; Romi Faslah (Al-Mudarris, 2025)
This article discusses the implementation of quality control systems in maintaining the effectiveness of Islamic non-formal education through a conceptual and analytical literature-based approach. Islamic non-formal education plays a strategic role in expanding access to lifelong learning and empowering communities through skill-based and entrepreneurial programs. However, the effectiveness of non-formal education institutions is often hindered by a limited number of professional educators, insufficient funding, and a weak institutional quality culture. Using a qualitative descriptive library research approach, this study synthesizes academic literature, policy documents, and national quality assurance frameworks related to non-formal education institutions, including Community Learning Activity Centers (PKBM) and Course and Training Institutions (LKP). The analysis conceptualizes the effectiveness of quality control systems not as empirically measured outcomes, but as a theoretical construct shaped by leadership commitment, stakeholder participation, and systemic regulatory support. From the perspective of Islamic education, quality control is interpreted as an ethical obligation (amanah) that integrates professional standards with moral responsibility and social accountability. The main contribution of this article lies in offering a conceptual framework that enriches the discourse on quality management in Islamic non-formal education by integrating sustainability principles with Islamic educational values.